The Rule of Al-Nahi in QS. Al-Māidah: 6 and 8:The Relevance of Ethics in Social Media in the Digital Era - Akib, Moh.; Maula, Nabila An'imatul (PT. Student Rihlah Indonesia, 2025)
This article discusses the principle of al-nahi (prohibition) in the context of QS. Al-Māidah verses 6 and 8, particularly its relevance to social media ethics in the Indonesian digital era. The purpose of this study is to analyze how the principle of al-nahi can be applied in the context of social media use, especially in preventing the spread of hoaxes, slander, and hate speech. This study uses a qualitative method with a thematic interpretation (maudhu'i) approach. The results show that the principle of al-nahi in QS. Al-Māidah verses 6 and 8 provides an important principle for building healthy social media ethics, namely by preventing actions that lead to moral, social, and religious damage. Verse 6 contains the importance of maintaining moral purity, for example, before posting or commenting, a person must ensure that their intentions are free from hatred, slander, or lies. Meanwhile, in verse 8, when a person wants to spread news or comment on a particular issue, they must maintain objectivity and not get carried away by emotions, and are prohibited from spreading hoaxes and hate speech. This prohibition reflects the urgency of maintaining justice and truth in digital communication.